Konflik Hukum Perdata Internasional dalam Kepemilikan Tanah oleh WNA di Indonesia: Studi atas Lex Rei Sitae dan Public Order - Septy Amelia Handayani; Desak Andini Parameswari; Lucky Dafira Nugroho (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Indonesia is a unitary state comprised of thousands of islands and vast seas. Land is a vital asset for both the people and the state; therefore, its control, use, and preservation must be regulated fairly to prevent misuse, particularly by foreign parties. This study focuses on the extent to which the limitations on land ownership by foreign nationals (FNs), as established by national law, can be effectively applied in cases occurring beyond Indonesia's jurisdiction.The aim of this research is to examine how the principle of lex rei sitae, the doctrine of cross-border inheritance law, and the concept of ordre public in Indonesian law interact with one another in order to formulate legal policies that uphold agrarian justice and national sovereignty, while also adapting to global changes. The findings of this study reveal that the principles of lex rei sitae and ordre public serve not merely as grounds for legal rejection, but as fundamental pillars in shaping land ownership policies for foreign nationals based on fairness, proportionality, and sustainability. By implementing a legal system that is firm, consistent, yet flexible, Indonesia is able to safeguard its national sovereignty while also fostering international trust as a rule-of-law state capable of facing global challenges without losing its national identity.